Production characteristics of a flock of East African Blackhead sheep - Sacker, G.D.; Trail, J.C.M. (1966)
Production characteristics, covering ewe breeding data; growth of lambs and use of correction factors for parity of dam, sex and type of birth of lamb; ewe milk production as measured by early lamb growth; effects of dry season on lamb weights and ewe milk production; repeatabilities and phenotypic correlations between lambs weights; and assessment of lamb mortality, were examined in a flock of East African Blackhead sheep maintained over an 11-year period in western Uganda. The ewes had an unrestricted mating season; age at first lambing was 532±8 days; mean overall lambing interval was 255±2.3 days and an average of 7 lamb crops per ewe were produced over the period from birth to 6 years of age. Lamb weight correction factors were worked out for parity of dam, sex and twinning, the mean weights of male single lambs were 5.6lb. at birth , 22.2lb. at 2 months, 34.2lb. at weaning and 52.9lb. at 1 year. Milk production as measured by lamb growth was significantly greater in ewes than in gimmers; ewes rearing twins produced significantly more milk than ewes rearing singles. Ewes milk production was significantly lower in the dry season than in the remainder of each year. Dry season did not appear to affect lamb birth weights or growth from 2 months to 5 months, but caused significantly lower growth rates during the main suckling period from birth to 2 months of age. The significant repeatability values were 0.100±0.032 for birth weight and 0.112±0.038 for weaning weight. The correlation between birth weight and 2-month weight was 0.279±0.035, birth weight and weaning weight was 0.194±0.038, 2-month weight and weaning weight 0.635±0.023 and weaning weight and weight at 1 year 0.504±0.033. The overall mortality rates to weaning were 20.1 per cent for singles from gimmers, 15.8 per cent for singles from ewes and 27.5 per cent for twins from ewes. The advantages and disadvantages of a controlled breeding season and the use of Dorset Horn blood for improved mutton production were discussed.